2013
DOI: 10.1186/1471-2180-13-4
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic properties of Lactobacillus jensenii engineered as a live vaginal anti-HIV microbicide

Abstract: BackgroundVaginal probiotics are investigated as a binary strategy for prevention of bacterial vaginosis and HIV. We applied an innovative experimental model using primary and immortalized human cervical and vaginal epithelial cells to assess the functional properties of Lactobacillus jensenii, a predominant constituent of the healthy vaginal microbiome, engineered to express the HIV-1 entry inhibitor modified cyanovirin-N (mCV-N). In this model bacteria colonize the epithelial cells over a period of 24-72 h. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 76 publications
2
28
0
Order By: Relevance
“…A vaginae did not grow under planktonic conditions but showed high numbers in the presence of colonised and TV-infected cells. Electron microscopy confirmed lack of cytotoxicity in our vaginal colonisation model, as previously shown,16 17 and also confirmed abundance of intracellular A vaginae (figure 1B) and P bivia (not shown). The ability of vaginal bacteria to reside inside the cervicovaginal epithelial cells is a phenomenon that warrants further investigation.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…A vaginae did not grow under planktonic conditions but showed high numbers in the presence of colonised and TV-infected cells. Electron microscopy confirmed lack of cytotoxicity in our vaginal colonisation model, as previously shown,16 17 and also confirmed abundance of intracellular A vaginae (figure 1B) and P bivia (not shown). The ability of vaginal bacteria to reside inside the cervicovaginal epithelial cells is a phenomenon that warrants further investigation.…”
Section: Resultssupporting
confidence: 89%
“…TV (1.25×10 5 parasites/cm 2 ), LPG (240 µg/ml) or CPI-GC (240 µg/ml) were then added, and epithelia-associated bacteria as well as immune responses were assessed after another 24 h. Synthetic TLR2/TLR6 ligand MALP-2 (25 nM; Alexis Biologicals) analogue of Mycoplasma fermentans lipopeptide macrophage activating lipopeptide was used as a pro-inflammatory control. At the end of each stimulation period, supernatants were unless specified collected for soluble mediators and epithelial cells were lysed for colony-forming units (CFU) counts, used for viability assessment or used for microscopy 16 17. For CFU counts, epithelial cells were washed twice with PBS and hypotonically lysed in HyPure water (Fisher) for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of lactobacilli (specifically L. crispatus and L. vaginalis) was associated with lower levels of proinflammatory cytokines in our study. This is consistent with previous observations about the noninflammatory nature of specific Lactobacillus species (50,51). These species were also associated with higher levels of the protective antimicrobial proteins SLPI and elafin in our study.…”
Section: Discussionsupporting
confidence: 82%
“…A nonvaginal Lactobacillus species induced production of proinflammatory protein MIP-3a [64]. Vaginal pathogens, associated with BV such as Atopobium vaginae and Prevotella bivia induced simultaneous NF-jB activation and upregulation of proinflammatory proteins in contrast to vaginal strains L. crispatus, L. acidophilus and L. jensenii [28,62]. BV is the most common vaginal infection among women of reproductive age.…”
Section: Resultsmentioning
confidence: 95%
“…The net effect of NF-jB activation depends on the cell and tissue properties, the interaction of intra-and extra-cellular factors, and the nature of the activating signal [60]. It has been previously shown that vaginal Lactobacillus species (L. crispatus, L. acidophilus and L. jensenii) can cause NF-jB activation and yet maintain low levels of IL-8 and RANTES [28,62]. L. jensenii can suppress IL-8 induced by TLR ligands [63].…”
Section: Resultsmentioning
confidence: 99%